Respiratory Syncytial Virus (RSV) and Intention to Recommend RSV Vaccination: A Cross-Sectional Survey of Cardiologists and Cardiac Nurses in Southern Italy - Domenico Ponticelli; Lorenzo Losa; Ippazio Cosimo Antonazzo; Anna Zampella; Fabio Di Marino; Gaetano Mottola; Mara Noemi Fede; Fortuna Gallucci; Roberto Magliuolo; Antonio Rainone; Antonella Arcari; Carmine Del Giudice; et al. (MDPI AG, 2024)
As respiratory syncytial virus (RSV) vaccine distribution gains traction in Europe and Italy, healthcare workers (HCWs) can strategize about vaccine promotion to increase uptake among patients at risk of RSV consequences, such cardiac patients. This cross-sectional survey investigated the knowledge about and attitude towards RSV and RSV vaccines, and the intention to recommend vaccination within a cardiological hospital in Italy. To explore factors associated with the outcomes of interest, multivariate logistic regression analyses were conducted. Of 197 invited HCWs, 78.2% returned the survey. The knowledge about market authorisation for new RSV vaccines for older adults (present in 46.9% of respondents) was significantly associated with the HCWs' age, education, and previous update on vaccinations. HCWs with a higher educational level and those with a positive attitude towards RSV vaccines safety reported a higher attitude towards the importance of vaccinating people at risk. The willingness of recommending RSV vaccination to patients (70.5% of respondents) was more likely in HCWs who were knowledgeable about market authorisation for RSV vaccines and in physicians. This tempestive research sheds light on current factors influencing the strategies of cardiac HCWs regarding RSV vaccination. The results suggest the need for training events on the protective role of RSV vaccination in cardiac patients.